Southeast Asian Anthropologies National Traditions and Transnational Practices - Thompson, Eric C.; Sinha, Vineeta (NUS Press, 2019)
Anthropology is a flourishing discipline in Southeast Asia. This book makes visible the development of national traditions and transnational practices of anthropology across the region. The authors are practising anthropologists with decades of experience in the intellectual traditions and institutions that have taken root in the region. Three overlapping issues are addressed in these pages. First, the historical development of traditions of research, scholarship, and social engagement across diverse anthropological communities of the region, which have adopted and adapted global anthropological trends to their local circumstances. Second, the opportunities and challenges faced by Southeast Asian anthropologists as they practise their craft in different political contexts. Third, the emergence of locally-grounded, intra-regional, transnational linkages and practices. The book contributes to a 21st-century, world anthropologies paradigm from a Southeast Asian perspective.